2023
DOI: 10.3390/plants12051163
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Key Metabolites and Their Pathways Revealed the Response of Alfalfa (Medicago sativa L.) Root Exudates to rac-GR24 under Drought Stress

Abstract: The rac-GR24, an artificial analog of strigolactone, is known for its roles in inhibiting branches, and previous studies have reported that it has a certain mechanism to relieve abiotic stress, but the underlying metabolic mechanisms of mitigation for drought-induced remain unclear. Therefore, the objectives of this study were to identify associated metabolic pathways that are regulated by rac-GR24 in alfalfa (Medicago sativa L.) and to determine the metabolic mechanisms of rac-GR24 that are involved in drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…However, when Bacillus inoculation and GR24 were combined, there was a significant improvement (see Figure 8). This is consistent with the results of a previous study, which showed that rac-GR24 treatment increased the soluble sugar content in alfalfa leaves compared to the control [124]. Another study found that low-light stress decreased cucumber leaves' soluble sugar and sucrose levels.…”
Section: Discussionsupporting
confidence: 92%
“…However, when Bacillus inoculation and GR24 were combined, there was a significant improvement (see Figure 8). This is consistent with the results of a previous study, which showed that rac-GR24 treatment increased the soluble sugar content in alfalfa leaves compared to the control [124]. Another study found that low-light stress decreased cucumber leaves' soluble sugar and sucrose levels.…”
Section: Discussionsupporting
confidence: 92%